Analisis Motivasi dan Etos Kerja Terhadap Kinerja Karyawan Food Fair Semarang - Krisnawati Setyaningrum Nugraheni; Tuwuh Adhistyo Wijoyo; YR Satatoe (Universitas Medan Area, 2020)
This study aims to analyze the motivation and work ethic of the performance of FF (Food Fair) Mall employees. The object of research is FF Mall Citraland Semarang employees. The sample used was 59 respondents who worked at FF Mall Citraland Semarang. The analysis used is multiple linear regression analysis. Regression results obtained with Y = 3,615 + 0,666 X1 + 0,338 X2. Motivation has a significant effect on the performance of FF Mall Citraland Semarang employees. Work ethic has a significant effect on the performance of FF Mall Citraland Semarang employees. Motivation and work ethic together towards FF Mall Citraland Semarang Employee Performance.